Analysis of New Students' Science Process Skills Readiness and Its Impact on Basic Physics 1 Learning Outcomes - Afriyani; Juniar Afrida; Zahriah (PTE FTK UIN Ar-Raniry, 2026)
Physics courses require mastery of Science Process Skills (SPS) as a foundation for developing conceptual understanding and scientific thinking skills. However, problems often exhibit heterogeneous practical skills due to differences in previous learning experiences. Therefore, this study aims to analyze the relationship between SPS and student learning outcomes in Basic Physics courses. This study used a quantitative approach with a correlational research design. A total sampling technique was used, involving 20 first-year students as participants. SPS data were collected through a science process skills test, while learning outcomes were obtained from final course grades. The results showed a significant positive relationship between SPS and learning outcomes, with a correlation coefficient of 0.431 (p = 0.029), indicating a fairly strong correlation. This indicates considerable variation in students' SPS levels, while academic grades tend to be relatively homogeneous. There is an imbalance between students' practical competencies and their cognitive achievements. In conclusion, SPS is significantly related to student learning outcomes in Basic Physics. Differences in SPS encourage the need for standardization of laboratory-based learning to improve the quality and equality of physics learning outcomes